From the perspective of: Functional Analysis of Lexical Bundles in Applied Linguistics ‎Research Articles ‎ - Jalilifar, Alireza; Ghoreishi, Seyed Mohammad (International Journal of English Studies, 2018)
The current study explored two levels of lexical bundles, core (i.e. general) and peripheral (i.e. domain specific), in a corpus of 200 applied linguistics research articles and examined the functions they serve. Using Antconc software, in total, 2563 lexical bundles were identified including 593 core bundles and 1370 peripheral bundles. These numbers account for 30% and 70% of the full list of bundles, covering 8.54% in comparison to 7.76% of one-million-word corpus respectively. Functional analysis revealed that core and peripheral bundles follow the same pattern, with text oriented bundles making it to the top of the list followed by research oriented and participant oriented bundles. Peripheral bundles surpassed core bundles, providing evidence for the existence of more diversity of peripheral bundles. Structural and functional correlates also showed that the form of lexical bundles is closely related to the functional use of the bundles rather than whether they are general or domain specific.